Chlamydia Protease-Like Activity Factor (CPAF): Characterization of Proteolysis Activity In Vitro and Development of a Nanomolar Affinity CPAF Zymogen-Derived Inhibitor - Bednar, Maria M. (2011)
During infection of epithelial cells, the obligate intracellular pathogen Chlamydia trachomatis secretes the serine protease CPAF into the host cytosol to regulate a range of host cellular processes through targeted proteolysis. Here we report the development of an in vitro assay for the enzyme and the discovery of a cell-permeable CPAF zymogen-based peptide inhibitor with nanomolar inhibitory affinity. Treating C. trachomatis-infected HeLa cells with this inhibitor prevented CPAF cleavage of the intermediate filament vimentin, and led to loss of vimentin-cage surrounding the intracellular vacuole. Because Chlamydia is a genetically intractable organism, this inhibitor may serve as a tool to understand the role of CPAF in pathogenesis.